Varamiento de cachalotes (Physeter macrocephalus) (Cetacea: Physeteridae) en la costa ecuatoriana por interacción con pesquerías - Haase, B.; Félix, F. (Instituto Oceanográfico de la Armada, Guayaquil, Ecuador, 1996)
El objetivo del presente trabajo es dar a conocer los varamientos de cachalotes en la costa ecuatoriana y mostrar que en algunos casos tales hechos tuvieron una relación directa con actividades pesqueras. Between 1987 and December 1993 fifteen stranding of the sperm whale (Physeter macrocephalus) were registered on the Ecuadorean continental coast. In eight cases an interaction with some type of fishing gear had occured previously, mainly with gillnets. In spite of the fact that the read number of interactions is unkown, it is supposed that the fisheries play an important role in the mortality of these animals. In at least three cases, the animals were taken to the beach by fishermen in orden to take some profit of them. The meat and the fat were used for bait, and parts of the animal such as the teeth and bones represent an increasing value on the market. Although the whales are protected by law in Ecuador, the additional income that the fishermen can get of a sperm whale which was caught accidentally could be a motive to convert this activity ino a directed, but illegal fishery. Incluye ref.bibl., ilus., tbls. Published